Structural and functional characterization of the PNKP–XRCC4–LigIV DNA repair complex. Issue 10 (27th April 2017) - Aceytuno, R. Daniel; Piett, Cortt G.; Havali-Shahriari, Zahra; Edwards, Ross A.; Rey, Martial; Ye, Ruiqiong; Javed, Fatima; Fang, Shujuan; Mani, Rajam; Weinfeld, Michael; Hammel, Michal; Tainer, John A.; et al.
Abstract: Non-homologous end joining (NHEJ) repairs DNA double strand breaks in non-cycling eukaryotic cells. NHEJ relies on polynucleotide kinase/phosphatase (PNKP), which generates 5΄-phosphate/3΄-hydroxyl DNA termini that are critical for ligation by the NHEJ DNA ligase, LigIV. PNKP and LigIV require the NHEJ scaffolding protein, XRCC4. The PNKP FHA domain binds to the CK2-phosphorylated XRCC4 C-terminal tail, while LigIV uses its tandem BRCT repeats to bind the XRCC4 coiled-coil. Yet, the assembled PNKP-XRCC4–LigIV complex remains uncharacterized. Here, we report purification and characterization of a recombinant PNKP–XRCC4–LigIV complex. We show that the stable binding of PNKP in this complex requires XRCC4 phosphorylation and that only one PNKP protomer binds per XRCC4 dimer. Small angle X-ray scattering (SAXS) reveals a flexible multi-state complex that suggests that both the PNKP FHA and catalytic domains contact the XRCC4 coiled-coil and LigIV BRCT repeats. Hydrogen-deuterium exchange indicates protection of a surface on the PNKP phosphatase domain that may contact XRCC4–LigIV. A mutation on this surface (E326K) causes the hereditary neuro-developmental disorder, MCSZ. This mutation impairs PNKP recruitment to damaged DNA in human cells and provides a possible disease mechanism. Together, this work unveils multipoint contacts between PNKP and XRCC4–LigIV that regulate PNKP recruitment and activity within NHEJ.